Employment relations and unions in public administration in Portugal and Spain: from reform to austerity - Stoleroff, A. (European Journal of Industrial Relations, 2013)
This article examines trade union responses to the transformation of employment relations in the public administration in Portugal throughout the Reform programmes launched after 2002 and the more recent austerity measures. It examines the relationship between conflict and concertation and analyses the perspectives and practices of the sector’s ideologically divided trade unions. It finally considers comparative issues emerging from the application of similar austerity packages in Portugal and Spain and contrasts their paths of employment relations and union action in public administration.